SIGNIFICANCE AND PERFORMANCE OF PROPERTY MARKETS IN MALAYSIA - Yop, Mohd Haris (PLANNING MALAYSIA, 2021)
The importance of the global real estate market has been widely debated over the last decade. Prior discussion has focused on various aspects of analysis used to evaluate the performance of the property market, such as statistical analysis, surveys, academic or industrial literature. As a result, it is also necessary to examine the global and Asian property markets while also evaluating the significance and performance of the Malaysian property market in comparison to other Asian markets to determine Malaysia’s international contribution to the global property market. The performance of Malaysia’s property market from 2015 to 2018 was examined in this study. Data was gathered using Thomson Router Data Stream from Real Capital Analytic, Asia Pacific Real Estate Association (APREA), World Economic Forum, and Transparency International, among others. The study’s findings will extend knowledge not only of the performance and significance of the Malaysian property market, but also of GDP growth, inflation rate, market ranking global, competitiveness business environment index, corruption perception, and risk and transparency index in Malaysia and across Asian countries. The overall results indicate that the performance and signs of the Malaysian real estate market were better compared to other Asian and developing markets.